Interference signal processing for dynamic displacement measurement with 1 ns time resolution. (14th December 2017) - Furukawa, Osamu; Tanaka, Yosuke
Abstract: We propose a novel signal processing method for a laser-interferometer-based displacement measurement system with significantly improved time resolution that enables us to measure transient state vibration with an instantaneous frequency of 100 MHz. In this method, a reference light is modulated by a sinusoidal waveform, and dynamic displacement is derived from the envelope curves of the interference signal. Using a phase modulator to emulate dynamic displacement with an instantaneous frequency of 100 MHz and a maximum peak-to-peak amplitude of over 100 nm, we confirmed that the proposed method can be used to measure fast dynamic displacement with 1 ns time resolution within 2.6 nm standard deviation.